Associated Factors of Obesity among Under-Five Children in Tangerang, Indonesia, 2024 - Putri Nabila; Meliana Sari (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The prevalence of obesity in Indonesia continues to rise. Childhood obesity has become one of the major public health concerns, as it affects children’s growth and long-term health status. Objective : This study aimed to determine the factors associated with obesity among under-five children. Research Methods/ Implementation Methods : The study was conducted among children living in the working area of Sukasari Primary Health Centre. This research employed a cross-sectional design involving 110 mothers with under-five children selected through purposive sampling. Data were analysed using the Chi-square test. Results : The results showed that the prevalence of obesity among under-five children was 27.3% (30 children). Hereditary factors, maternal education, maternal occupation, parental income, fast food consumption, consumption of sweet foods and beverages, and snack consumption (p-value < 0.05) were significantly associated with obesity among under-five children. Conclusion/Lesson Learned : Based on these findings, health facilities should strengthen parental education, particularly regarding complementary feeding (MP-ASI), as it plays a crucial role in shaping children’s early eating habits.